Structural features of word-formation nests with odourativnymi roots in Ukrainian II halves XIX century (on «Dictionary of Ukrainian» B. Grinchenko) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
Research of history of leksicheskeogo composition of Ukrainian is impossible without finding out of history of separate semantic grup. The analysis of word-formation nests with odorativnymi roots (on a dictionary B. Grinchenko) presents the vocabulary of odour in Ukrainian II halves of XIX of century.
Keywords: odour; odourative vocabulary; word-formation nest; derivatives; root